The Impact of Tax Havens on Domestic Legislative Regulation in Selected States - Akylbek Ilyas; Gurgen Gukasyan; Sergei Chernov; Vladimir Kosarev (BESTUUR, 2025)
The expansion of the offshore economy poses significant challenges to national tax systems by facilitating tax evasion, profit shifting, and income concealment, thereby undermining fiscal sovereignty. This manuscript examines the impact of tax havens on national tax legislation and analyzes legal responses to offshore-based tax avoidance within domestic legal frameworks. The study applies a normative juridical method by conducting comparative legal analysis and statutory review of recent legislative developments in the United Kingdom, the European Union, and the Russian Federation. The findings demonstrate, first, that the OECD Base Erosion and Profit Shifting (BEPS) Action Plan functions as a central reference for tax law reform in both OECD and non-OECD jurisdictions and, second, that national legal systems increasingly strengthen regulatory mechanisms to enhance corporate transparency, particularly through mandatory disclosure of ultimate beneficial ownership and expanded information-exchange obligations. These trends indicate a growing convergence of domestic tax laws toward international standards aimed at preventing offshore tax abuses and reinforcing the effectiveness of tax enforcement.